Fenomena Baby Blues Sebagai Faktor Pemicu Perilaku Self-Harm dan Kekerasan Pada Anak (Studi Kasus UPT PPA Prov. Riau Tahun 2025) - Maisyaroh, Elsa; Rio Tutrianto (UIR PRESS, 2026)
This study examines the phenomenon of baby blues as a triggering factor for self-harm behavior and violence against children in Pekanbaru City. The research problem stems from the low level of public understanding of baby blues, which is often perceived as a mild emotional disturbance following childbirth, even though it can develop into a more serious psychological disorder. This study aims to determine the influence of baby blues on the emergence of self-harm behavior and violence against children. The research employed a qualitative method with a descriptive research design. The study was conducted at the Regional Technical Implementation Unit for the Protection of Women and Children (UPT PPA) of Riau Province through interviews, observations, and documentation involving informants related to women and children's cases. The findings indicate that hormonal changes, physical exhaustion, psychological pressure, lack of family support, and socioeconomic conditions are the main factors contributing to baby blues. These conditions lead to emotional instability, stress, and loss of self-control, thereby triggering self-harm behavior and violence against children. This study emphasizes the importance of family support and mental health services for postpartum mothers.